Mast cells have no impact on cutaneous leishmaniasis severity and related Th2 differentiation in resistant and susceptible mice. Issue 1 (6th November 2015) - Paul, Christoph; Wolff, Svenja; Zapf, Thea; Raifer, Hartmann; Feyerabend, Thorsten B.; Bollig, Nadine; Camara, Bärbel; Trier, Claudia; Schleicher, Ulrike; Rodewald, Hans‐Reimer; Lohoff, Michael
Abstract : The genus leishmania comprises different protozoan parasites which are causative agents of muco‐cutaneous and systemic, potentially lethal diseases. After infection with the species Leishmania major, resistant mice expand Th1 cells which stimulate macrophages for Leishmania destruction. In contrast, susceptible mice generate Th2 cells which deactivate macrophages, leading to systemic spread of the pathogens. Th‐cell differentiation is determined within the first days, and Th2 cell differentiation requires IL‐4, whereby the initial IL‐4 source is often unknown. Mast cells are potential sources of IL‐4, and hence their role in murine leishmaniasis has previously been studied in mast cell‐deficient Kit mutant mice, although these mice display immunological phenotypes beyond mast cell deficiency. We therefore readdressed this question by infecting Kit‐independent mast cell‐deficient mice that are Th1 (C57BL/6 Cpa Cre ) or Th2 (BALB/c Cpa Cre ) prone with L. major . Using different parasite doses and intra‐ or subcutaneous infection routes, the results demonstrate no role of mast cells on lesion size development, parasite load, immune cell phenotypes expanding in draining lymph nodes, and cytokine production during murine cutaneous leishmaniasis. Thus, other cell types such as ILCs or T cells have to be considered as primary source of Th2‐driving IL‐4.